Solo Islamic Park - Huda, Amiratul; , Dr. Ir. Widyastuti Nurjayanti, MT (2016)
The city was a Solo those at the regional II located in the Central Java. Is a lowland located in the slope the Lawu and the Merapi explosion with the height of about 92 m above sea leve. Every city must have 30% space of the total area of, with details 20% public green settlement. An open space in Solo, in the form of green zone (RTH) and non green space (RTNH), both planned and unplanned of alun-alun, the pedestrian, Fort Vastenburg, Monuments Solo Press, Balaikambang Park, Sekartaji Park, 45 Banjarsari Monument, open space UMS and UNS and Parks on to the sub Solo. See the city Solo Majority of muslim made the need for an open space community support activity by providing green space. Supported by the Islamic school, Islamic boarding school, and mosque acroee the city planning Solo "Solo Islamic Park" can be a landmark new to the Solo. To the concept of Islam referring to Al-Qur'an and Hadist this park not only as tourist destination course, "Solo Islamic Park" are education as outbound facilities sports. Form the building the octagon in the middle of region and other buildings having the different form. The Islamic architecture, building make use of the site as natural cooling and lighting natural. On landscape furnished with site furniture: shelters, park bench, the information board, parking bicycles, the trash, and the park. Plant planted in landscape of flower and plant mentioned by Al-Qur'an like palm, tin and shape of landscape of form Islamic ornament. Keyword : Landscape, Area, Park, Islamic